Investigating of density effect on the growth and survival of Caspian Kutum, Rutilus frisii (Kamensky, 1901) pre-fattening in freshwater concrete ponds - Alireza Valipour; Danial Gorouhi; Mohammad Sayad Bourani; Ali Hasanpour (تغذیه آبزیان)
Introduction: The Caspian Kutum (Rutilus frisii) is a unique species of bony fish native to the Iranian coastal of the Caspian Sea, which can be a suitable fish for introduction to the aquaculture industry in Iran. Considering its marketability, commercial importance and high nutritional value, the Iranian Fisheries Research Institute, aimed to carry out an experimental study with the aim of increasing production and supplies, reducing fishing pressure and protecting its natural stocks in the Caspian Sea and finally, introducing as a new and strategic species to the country's aquaculture industries. Materials and methods: In this study, the growth performance and survival rate of cultured Kutum fry, with an initial average weight of 1.78 ± 0.66 g, were evaluated in two different densities: 25 and 50 fish/m2, for a period of 110 days in some concrete channel ponds with an approximate volume of 8 m3. The ponds received a constant water flow from an agricultural irrigation channel at the Restoration and Protection of Fish Genetic Resources of Shahid Ansari Center, Rasht, Iran. Results and discussion: The growth rate showed a significant inverse relationship with density in the experimental treatments (p<0.05), with average weight gain of 1364.84 ± 16.19 and 653.82 ± 44.29 g in the treatments 1 and 2, respectively. The food conversion ratio exhibited a direct relationship with density, displaying a significant difference with averages of 1.93 ± 0.13 in low- and 5.41 ± 0.56 in high-density treatments. Also, the results indicated that increased density led to a significant drop in body length gain indices, specific growth rate, and daily growth rate (p<0.05). There was a significant difference between treatments 1 and 2 in terms of survival rate at the end of the rearing period, with the values of 84.62 ± 3.52% and 77.95 ± 1.35%, respectively. Conclusions: In general, the results of this study confirmed that the rearing of Kutum fry at a density of 25 fish/m3 in concrete ponds with freshwater is more suitable to achieve better performance. Conflicts of interest: Authors have no conflict of interest to declare for the publication of the present research. Acknowledgments: We are very grateful to the colleagues of Aquaculture and Ecology Departments of Inland Water Aquaculture Research Center and also the colleagues of the Shahid Ansari Fish Genetic Resources Restoration and Protection Center in Rasht.